Association of Body Weight Variability With Progression of Coronary Artery Calcification in Patients With Predialysis Chronic Kidney Disease - Suh, Sang Heon; Oh, Tae Ryom; Choi, Hong Sang; Kim, Chang Seong; Bae, Eun Hui; Oh, Kook-Hwan; Lee, Kyu-Beck; Han, Seung Hyeok; Sung, Suah; Ma, Seong Kwon; Kim, Soo Wan (Frontiers in Cardiovascular Medicine, 2022)
Background: We investigated whether high body weight variability (BWV) is associated with higher prevalence of coronary artery calcification (CAC) or more rapid progression of CAC in patients with pre-dialysis chronic kidney disease (CKD). Methods: A total of 1162 subjects from a nationwide prospective cohort of pre-dialysis CKD were analyzed. The subjects were divided into the tertile (T1, T2, and T3) by BWV. CAC was assessed at the baseline and at 4-year follow-up by computed tomography scan. Rapid progression of coronary artery calcification was defined as increase in coronary artery calcium score (CACS) more than 200 Agatston units during 4-year follow-up. Results: One-way analysis of variance reveled that CACS change during follow-up period is significantly higher in the subjects with high BWV, although CACS at the baseline and at 4-year follow-up was not different among the tertile groups by BWV. Logistic regression analysis revealed that, compared to low BWV (T1), both moderate (T2, adjusted odd ratio (OR) 2.118, 95% CI 1.075 to 4.175) and high (T3, adjusted OR 2.602, 95% CI 1.304 to 5.191) BWV was associated with significantly increased risk of rapid progression of CAC. Importantly, the association between BWV and progression of CAC remained robust even among the subjects without significant BW gain or loss during follow-up periods (T2, adjusted OR 2.007, 95% CI 1.011 to 3.984; T3, adjusted OR 2.054, 95% CI 1.003 to 4.207). Conclusions: High BWV is independently associated with rapid progression of CAC in patients with pre-dialysis CKD.